2018
DOI: 10.1590/0034-7167-2017-0709
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anxiety and depression on morbidity and mortality of patients with coronary syndrome

Abstract: Objective: Evaluate the impact of anxiety and depression on morbidity and mortality of patients with acute coronary syndrome. Method: Retrospective cohort study, with follow-up of two years, conducted with 94 patients. The morbidity and mortality (readmission, myocardial revascularization, and death) was evaluated immediately after discharge and after one and two years. Anxiety and depression were evaluated by the State-Trait Anxiety Inventory and by Beck’s Depression Inventory. The Kaplan-Meier estimator and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
1
0
2
Order By: Relevance
“…17,20,22 Unlike other studies, in which the main stressor was pain (physical discomfort dimension), 9,11,17,20,22 this study showed that the main stressors were related to psychological distress (being unaware of ICU length of stay, being unable to fulfil family roles, missing husband or wife, financial concerns, and loss of self-control). Such findings are similar to those of two different studies that identified a high frequency of anxiety and depression in patients with ACS, 35,36 pointing out measures aimed at reducing psychological stressors in ICUs such as effective and safe communication 23 and inclusion of family members in patients' treatment decisions, in clinical discussions, and also in certain aspects of care, such as assistance with food and body hygiene. 37,38 This is justified by the fact that reducing stressors may lead to lower anxiety levels, as pointed in the conclusion of a study that assessed stressors and their relationship to anxiety among patients undergoing cardiac surgery.…”
Section: Discussionsupporting
confidence: 87%
“…17,20,22 Unlike other studies, in which the main stressor was pain (physical discomfort dimension), 9,11,17,20,22 this study showed that the main stressors were related to psychological distress (being unaware of ICU length of stay, being unable to fulfil family roles, missing husband or wife, financial concerns, and loss of self-control). Such findings are similar to those of two different studies that identified a high frequency of anxiety and depression in patients with ACS, 35,36 pointing out measures aimed at reducing psychological stressors in ICUs such as effective and safe communication 23 and inclusion of family members in patients' treatment decisions, in clinical discussions, and also in certain aspects of care, such as assistance with food and body hygiene. 37,38 This is justified by the fact that reducing stressors may lead to lower anxiety levels, as pointed in the conclusion of a study that assessed stressors and their relationship to anxiety among patients undergoing cardiac surgery.…”
Section: Discussionsupporting
confidence: 87%
“…The sequelae of under-treatment for depression and anxiety are severe and growing in the United States [11][12][13][14]. In the past two decades, "deaths of despair" (e.g., mortality attributed to drug overdoses, suicide, and alcoholic liver disease) have increased between 56% and 387% [15].…”
Section: Editorialmentioning
confidence: 99%
“…É comprovado que síndromes psiquiátricas, como a depressão estão muito presentes em pacientes portadores de síndrome coronariana aguda (SCA) (ALTINO et al, 2018).Tal relação é comprovada,pois vários estudos(prospectivos e meta-análises) mostram que existe uma intrínseca associação entre doenças arteriais coronarianas e transtornos mentais.Em tal viés,pautando-se na medicina baseada em evidências científicas,pode-se citar que a incidências de doenças cardiovasculares e cerebrovasculares são significativamente maiores em pacientes com transtornos mentais,como o transtornos depressivos (GAFAROV; ZAHODNE, 2017). Além disso, um estudo prospectivo evidenciou expressivo percentual de depressão nas pessoas que tinham cardiopatias e necessitavam de revascularização coronariana.Tal percentual só cresceu diante do processo de revascularização (KORBMACHE et al, 2013).…”
Section: Introductionunclassified
“…Desse modo, é importante enfatizar que, mesmo tratando-se de distúrbios distintos, muitas vezes aparecem em conjunto e, diante de tal associação, pode haver preditores significativos de pior prognóstico e maior índice de mortalidade (ALTINO et al, 2018).…”
Section: Introductionunclassified